Habituation Mitigates Adverse Effects of Heat Stress in Broiler Chicken During the Hot-Dry Season - Ogundeji Tunde; Ayo Joseph Olusegun (Folia Veterinaria)
Heat stress is a significant challenge in broiler chicken production, particularly in tropical and subtropical regions. This study evaluates the effectiveness of habituation in mitigating adverse effects of heat stress in broiler chickens during the hot-dry season. Sixty-day-old male broiler chicks (Arbor Acres) were randomly divided into control (n = 30) and habituated groups (n = 30). The habituated group was subjected to 4 days of habituation training from days 17 to 20. The two groups were subjected to tonic immobility (TI) test on day 21. Heterophil-to-lymphocyte (H:L) ratio, serum heat-shock protein 70 (Hsp70) expression, and erythrocyte osmotic fragility were assessed after the TI test. The results indicated that the thermal environment during the study period was characterised by high dry-bulb temperatures and high temperature-humidity index (THI), indicating significant thermal challenge on the broiler chickens. Habituated chickens showed significantly reduced TI durations compared to control. The H:L ratio and serum Hsp70 concentrations were markedly decreased (P < 0.05) in habituated chickens relative to controls. There was decreased (P < 0.05) erythrocyte membrane fragility in the habituated group, with reduced haemolysis compared to the control group. In conclusion, these findings show that the adverse effects of heat stress during the hot-dry season was mitigated in the habituated broiler chickens, as evidenced by reduced TI durations, a lower H:L ratio, decreased serum Hsp70 concentrations, and enhanced erythrocyte membrane stability. The study highlights the importance of habituation as a behavioural strategy in reducing sensitivity to heat stress in broiler chickens.